Effect of Humo Backter-A and spraying the GPR (Quick) on growth and yield of Squash (Cucurbita pepo L.) under green house conditions - Kadum, Ryad K.; .Abdel- Raheem, Hadyl A.; Jarallah, Marwoa H.; hashim, Zaied J. (Journal of Kerbala for Agricultural Sciences, 2017)
A factorial experiment was conducted during the season of 2013/2014 in green house to study the effect of HumoBackter-A at 4 liveles (0,1,2,3) ton.hectar-1 A and spraying the GPR (Quick) (0 , 0.05) on growth and yield of Squash var. Carisma, by using R.C.B.D design with 4 replicates. Results showed that the addition of HumoBackter-A, spraying the GPR (Quick) or their interaction had a significant effect on growth and yield, but the highest average of plant length, stem thick, leaves number, leaf area , fruit number, fruit weight, total yield per plant and hectar realized at the intraction of 3 ton of HumoBackter-A./ha-1 with Quick which gave 78.75cm , 22.25 leaf , 141.04 dec2, 14.25 fruit, 137.04 gm, 1.953 kg.plant-1 and 37.50 ton. hectar-1 respectively while the control treatment gave the lowest average of these properties.